29.8k views
2 votes
Simplify (2x^2 + x + 4)+(-3+7x + 8x^2)
i know how to im just lazy​

2 Answers

5 votes

Answer:

10 x^2 + 8 x + 1

Explanation:

Simplify the following:

8 x^2 + 2 x^2 + 7 x + x - 3 + 4

Grouping like terms, 8 x^2 + 2 x^2 + 7 x + x - 3 + 4 = (2 x^2 + 8 x^2) + (x + 7 x) + (4 - 3):

(2 x^2 + 8 x^2) + (x + 7 x) + (4 - 3)

2 x^2 + 8 x^2 = 10 x^2:

10 x^2 + (x + 7 x) + (4 - 3)

x + 7 x = 8 x:

10 x^2 + 8 x + (4 - 3)

4 - 3 = 1:

Answer: 10 x^2 + 8 x + 1

User Gulty
by
5.5k points
4 votes

Answer:


10 {x}^(2) + 8x + 1

Explanation:


2 {x}^(2) + x + 4 -3 + 7x + 8 {x}^(2) \\ = 2 {x}^(2) + 8 {x}^(2) + x + 7x + 4 - 3 \\ = 10 {x}^(2) + 8x + 1

User Nikeya
by
5.0k points